2019
DOI: 10.1097/brs.0000000000002969
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Rapidly Progressive Neurological Deterioration in Cervical Spondylotic Myelopathy

Abstract: Study Design. A retrospective single-center study. Objective. This study sought to clarify the risk factors and to evaluate the surgical outcome in patients with rapidly progressive cervical spondylotic myelopathy (rp-CSM). Summary of Background Data. CSM is a degenerative spine disease presenting a slow development of myelopathy. Some patients, however, show rapidly progressive neurological deterioration (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…The prognosis of patients with rapid progressive CSM is quite different among previous studies, Morishita reported that the preoperative JOA score is 5.4 and 9.6 at 1 year after surgery, which were signi cantly lower than in chronic CSM which were 10.1 and 12.9, respectively, and they concluded that prognosis of rp-CSM group was inferior than those in c-CSM group [3]. However, in the study of Takasawa [4] , JOA score was 5.7 preoperative and 12.9 after one year surgery (improvement rate was 64.5%) in rp-CSM group and 10.1 preoperative and 12.8 after one year surgery (improvement rate was 40.7%) in c-CSM, they reached a conclusion that patients with rp-CSM can get better recovery than those in c-CSM. In present study, The mJOA scores in rp-CSM group and c-CSM group were 6 and 12 before surgery, 8 and 14 at 1 week, 9 and 14 at 1 month, 10 and 15 at 3 month, 12 and 15 at 6 month and 12 and 15 at 1 year after surgery, respectively ,the mJOA scores at each follow-up time points in rp-CSM were signi cantly lower than those in c-CSM group.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The prognosis of patients with rapid progressive CSM is quite different among previous studies, Morishita reported that the preoperative JOA score is 5.4 and 9.6 at 1 year after surgery, which were signi cantly lower than in chronic CSM which were 10.1 and 12.9, respectively, and they concluded that prognosis of rp-CSM group was inferior than those in c-CSM group [3]. However, in the study of Takasawa [4] , JOA score was 5.7 preoperative and 12.9 after one year surgery (improvement rate was 64.5%) in rp-CSM group and 10.1 preoperative and 12.8 after one year surgery (improvement rate was 40.7%) in c-CSM, they reached a conclusion that patients with rp-CSM can get better recovery than those in c-CSM. In present study, The mJOA scores in rp-CSM group and c-CSM group were 6 and 12 before surgery, 8 and 14 at 1 week, 9 and 14 at 1 month, 10 and 15 at 3 month, 12 and 15 at 6 month and 12 and 15 at 1 year after surgery, respectively ,the mJOA scores at each follow-up time points in rp-CSM were signi cantly lower than those in c-CSM group.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have shown that 82% and 56% of CSM patients will not experience severe neurological deterioration 5 years and 10 years after systematic conservative treatment [2]. However, neurological function of some CSM patients develop to severe dysfunction (such as unable to button shirt or walk) in a very short time without any trauma, which called in previous studies as rapid progressive CSM (rp-CSM) [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cases of patients visiting our hospital between January 2010 and January 2014 were retrospectively reviewed. rp-CSP was defined as when the patients had a course of CSM less than 1 month and suffered rapidly progressive neurological deterioration, causing difficulty in maintaining a standing posture or walking without support [4,5]. c-CSM was defined as when the patients had a course of CSM of more than 1 month [4,5].…”
Section: Population Selectionmentioning
confidence: 99%
“…A few patients with CSM suffered rapidly progressive neurological deterioration, particularly with walking disorders. Compared with chronic CSM (c-CSM), there have been few reports on the characteristics of rapidly progressive CSM (rp-CSM) [4,5]. Therefore, it is important for us to recognize rp-CSM and the pathogenesis of rp-CSM.…”
Section: Introductionmentioning
confidence: 99%